"I've learned to look at things in a different way": exploring patients' perspectives on participation in physiotherapist delivered integrated stress inoculation training and exercise for acute whiplash. Issue 18 (28th August 2022) - Silva Guerrero, Alma Viviana; Setchell, Jenny; Maujean, Annick; Sterling, Michele
Abstract: Purpose: To explore patient perspectives of the integrated intervention (intervention arm) of a recent randomised clinical trial that found clinically relevant and sustained benefits of a physiotherapist delivered integrated stress inoculation training (SIT) and exercise for people with acute whiplash-associated disorders (WAD) and at risk of poor recovery. Material and methods: Twelve patients from the 53 who participated in the SIT and exercise arm of a randomised controlled trial (StressModex RCT) participated in semi-structured interviews. Data were analysed using inductive thematic analysis. Results: Five main themes were identified: "balance between the physical and psychological components, " "dealing with stress, " "coping with the injury, " "pain relief and return to function, " and "elements enhancing therapeutic alliance." Conclusions: The majority of patients found the SIT techniques to be helpful in managing stress and pain, coping with their injury, and returning to function. The patients also found the exercises useful and acknowledged the importance of both the physical and the psychological aspects of whiplash injury. IMPLICATIONS FOR REHABILITATION: Patients with acute WAD at risk of poor recovery welcomed the inclusion of psychological strategies as part of physiotherapy treatment. The patients nominated both the psychological (SIT) component and exercise as assisting them with their stress, pain, and recovery. Physiotherapists could consider including strategies targeting early stress responses in their management of patients with acute WAD.